2012
DOI: 10.7705/biomedica.v32i4.421
|View full text |Cite
|
Sign up to set email alerts
|

Actitudes, conocimientos y creencias del paciente hipertenso respecto a la medicación antihipertensiva

Abstract: Introducción. La hipertensión arterial es uno de los grandes problemas de salud pública. Una de las principales razones del escaso avance en la efectividad de las intervenciones es la falta de conocimiento de los factores determinantes psicológicos y sociales, como son las creencias sobre la enfermedad y su tratamiento. Objetivo. Valorar las actitudes del paciente respecto al tratamiento antihipertensivo y sus creencias. Materiales y métodos. Se llevó a cabo un estudio transversal descriptivo en una muestra al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
4
0
8
Order By: Relevance
“…Thus, it is essential that each hypertensive patient and anyone at high risk for developing CKD should perceive the seriousness of the disease and be committed in a self-care management process, starting from obtaining efficient knowledge, following positive attitudes and healthier practices and being compliant to prescribed drugs. More importantly, awareness programs for the whole population and not only for hypertensive patients should be held everywhere in Palestine, starting from school education up to promoting the role of nurses and doctor-patient relationship in providing knowledge and health advices to every patient especially those at high risk for developing CKD [9]. Greater efforts should be done to implement a screening protocol for high-risk patients in Palestine, hoping to slow down the rising numbers of CKD patients and build up a healthy society.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is essential that each hypertensive patient and anyone at high risk for developing CKD should perceive the seriousness of the disease and be committed in a self-care management process, starting from obtaining efficient knowledge, following positive attitudes and healthier practices and being compliant to prescribed drugs. More importantly, awareness programs for the whole population and not only for hypertensive patients should be held everywhere in Palestine, starting from school education up to promoting the role of nurses and doctor-patient relationship in providing knowledge and health advices to every patient especially those at high risk for developing CKD [9]. Greater efforts should be done to implement a screening protocol for high-risk patients in Palestine, hoping to slow down the rising numbers of CKD patients and build up a healthy society.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Effective screening methods, better communication with patients, frequent check-ups and compliance to drugs and healthy practices are all essential to achieve success in management but unfortunately these are actually real challenges [8]. Moreover studies showed that many of the hypertensive patients forget to take the prescribed medication occasionally thus emphasizing the great role of communication strategies of health professionals and the necessity of improving doctor-patient relationship [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Enero-Junio de 2015;7(1): 32-38 reciben del personal de salud ha contribuido para mejorar su estado de salud; lo cual comparando estos resultados con los obtenidos en la investigación de Acosta 3 y Buendía 7 , se observó discrepancias ya que el 45,4% planteó recibir los beneficios parcialmente y al 3% le resultó indiferente el tratamiento y el alrededor del 48 % de los pacientes refiere olvidar en algún momento tomar el medicamento antihipertensivo.…”
Section: Rfs Revista Facultad De Saludunclassified
“…14 Outro trabalho concluiu que a aliança terapêutica (dimensões cognitiva e emocional da relação médico-paciente) está fortemente associada à adesão e ao nível de satisfação do paciente com o tratamento. 15 Nesse sentido, o melhor controle pressórico em pacientes com vínculo com um médico poderia ser explicado não apenas pelo vínculo em si, mas por uma maior adesão ao tratamento nestes pacientes.…”
unclassified
“…Um estudo que avaliou a opinião de hipertensos encontrou alto grau de ignorância destes quanto à doença e concluiu que, se os médicos tivessem mais tempo para os pacientes, poderiam receitar menos medicamentos. 15 Outro estudo concluiu que a restrição da comunicação a aspectos biomédicos contribui para uma relação impessoal, sem diálogos, escutas, responsabilização e subjetividades, dificultando assim o estabelecimento do vínculo.…”
unclassified